Hubungan Efikasi Diri dan Motivasi Belajar Dengan Hasil Belajar Biologi Peserta Didik di SMA Negeri 1 Kecamatan Komodo Kabupaten Manggarai Barat - Amandus, Valerianus; Ihsan, Ikhlashul; Nurhidaya, Nurhidaya (Universitas Khairun, 2024)
This research aims to determine the relationship between self-efficacy and learning motivation with the biology learning outcomes of science class students at Komodo State High School. This type of ex-post facto research is quantitative descriptive. The independent variables in this research are self-efficacy (X1), learning motivation (X2) while the dependent variable is learning outcomes (Y). The sample for this research was 206 students in class X and XI Science at SMA Negeri 1 Komodo using a supportive random sampling technique. This research was conducted in August - September 2024. Research data was obtained using self-efficacy and learning motivation questionnaires. The data analysis technique is analysis (descriptive statistics) with the help of the SPSS (Statistical Package for Social Science) version 25 for Windows program. Based on the results of inferential statistical analysis, a significance value of 0.000 0.05 was obtained. It can be concluded that self-efficacy and learning motivation have a positive and significant relationship to the biology learning outcomes of students in classes X and XI Science at SMA Negeri 1 Komodo.